An efficient synthesis of 2, 4, 7-trisubstituted pyrimido[1, 2-a][1, 3, 5]triazin-6-ones1. (2nd June 2015) - Sachdeva, Nikhil; Dolzhenko, Anton V.; Lim, Seow Joo; Ong, Wee Ling; Chui, Wai Keung
<x xml:space="preserve">Abstract</x> A practical synthesis of 3, 4-dihydro pyrimido[1, 2-a][1, 3, 5]triazin-6-ones, experimental and theoretical assessment of their tautomeric preferences and biological activity results are presented.